Quality of Life after Type A Aortic Dissection Surgery in the United Kingdom: The QUADS Study - Ripoll, Brianda; Olayiwola, Adeyemi; Kalra, Sanjeev; Syed, Aidil; Capoccia, Massimo; Ahmed, Shaheen; Koulouroudias, Marinos; Mocanu, Ioan; Clark, Stephen; Deglurkar, Indu; Elmahdy, Walid; Hyde, Jonathan; Nicou, Niki; Attar, Nawar Al; Cale, Alexander; Loubani, Mahmoud; Oo, Aung Ye; Lopez-Marco, Ana (AORTA, 2024)
Background Acute Type A aortic dissection (TAAD) is a life-threatening condition that carries significant mortality and morbidity; a proportion of the survivors might require further aortic procedures in the mid-/long-term follow-up. Quality of life (QoL) after TAAD is not well studied. Quality of life after Type A Aortic Dissection Surgery (QUADS) is the first multicentre study to assess QoL in survivors of surgically treated TAAD.Methods A tailored questionnaire for survivors of TAAD was designed with patient and public involvement. Patients who underwent surgery from 2018 to 2022 in eight United Kingdom centres were invited to participate. Preoperative, intraoperative, and postoperative prospectively collected data were collated and analyzed retrospectively. The data were analyzed with SPSS v29. Patient's questionnaire was validated with a Cronbach's alpha analysis, exploratory factor analysis, and AMOS confirmatory factor analysis. Three groups were created according to QoL (Good, Fair, Poor).Results A total of 162 patients were recruited. Majority were male with a mean age of 63 years (24–92). Surgical procedures for TAAD were root and ascending aorta replacement (n = 61, 38%), ascending (n = 81, 50%), and/or arch replacement (n = 20, 12%). Eleven patients (7%) required later intervention. Patient's answers regarding overall QoL were good (n = 67, 41%), fair (n = 89, 55%), and poor (n = 6, 4%). Neurological complications, circulatory arrest duration, reoperation for bleeding, postoperative myocardial infraction, arrhythmias, wound infection, and patient destination at discharge have been identified as main variables impacting on QoL after TAAD surgery across different domains of this questionnaire.Conclusion QUADS questionnaire is the first tailored and validated questionnaire for TAAD survivors. Results in the United Kingdom population suggest that it is a useful tool to assess QoL after TAAD surgery.
Keywords: Type A aortic dissection; quality of life; aortic surgery; reintervention; multicenter study